2009
DOI: 10.1007/s11148-009-9184-x
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of aluminosilicate refractories by molten aluminum and melts based upon it in melting and casting units

Abstract: Corrosion mechanisms are proposed for aluminosilicate refractories by molten aluminum taking account of new ideas about physicochemical reaction of molten aluminum with refractory. With a negative volumetric effect for aluminum reactions with components of aluminosilicate refractories reaction products will not form a continuous film, and with a positive volumetric effect the reaction products will split pores and cause material cracking. A porous aluminum oxide film will not be a barrier for the reaction of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…[21,46] Amorphous phases undergo reactions with molten metals more easily because of the higher numbers of dislocations and boundary defects, and thus, the kinetics of the reactions between the molten metal and refractory are enhanced in this case. [44] At the same time, glassy phase formation increases the density and strength of the refractory at low temperatures.…”
Section: B Kinetic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21,46] Amorphous phases undergo reactions with molten metals more easily because of the higher numbers of dislocations and boundary defects, and thus, the kinetics of the reactions between the molten metal and refractory are enhanced in this case. [44] At the same time, glassy phase formation increases the density and strength of the refractory at low temperatures.…”
Section: B Kinetic Considerationsmentioning
confidence: 99%
“…[2][3][4] Wollastonite is resistant to molten aluminum alloy and has been shown to prevent metal penetration and corundum growth in the refractory material. [16] The use of wollastonite is based on the assumption that calcium silicates act as a barrier against the oxidation of molten aluminum. [17] Limited work has been carried out on the use of calcium oxide (CaO) as the additive for aluminum casting refractories.…”
Section: Introductionmentioning
confidence: 99%
“…2.13. It is also mentioned by Yurkov [70] and Allaire [71] that the sodium is oxidized again via either direct oxidation (>10" 19 atm P 02 ), or reduction of other impurities such as SiO 2 . etc.…”
Section: Oamentioning
confidence: 99%
“…It was observed that corrosion under dynamic conditions is more severe than it is under static conditions. Other researchers [70][71][72] who studied the corrosion of aluminosilicate refractories by molten aluminum also discussed the impact of impurities such as iron oxide and sodium oxide on the corrosion resistance of refractories. It is reported in these studies that Na2O is one of the most important impurity in alumina.…”
Section: Oamentioning
confidence: 99%
See 1 more Smart Citation